2017
DOI: 10.1080/10256016.2017.1345902
|View full text |Cite
|
Sign up to set email alerts
|

Development of a field-deployable method for simultaneous, real-time measurements of the four most abundant N2O isotopocules

Abstract: Understanding and quantifying the biogeochemical cycle of NO is essential to develop effective NO emission mitigation strategies. This study presents a novel, fully automated measurement technique that allows simultaneous, high-precision quantification of the four main NO isotopocules (NNO, NNO, NNO and NNO) in ambient air. The instrumentation consists of a trace gas extractor (TREX) coupled to a quantum cascade laser absorption spectrometer, designed for autonomous operation at remote measurement sites. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Data availability. Data are available at https://doi.org/10.17605/ OSF.IO/QPRJZ (Ibraim et al, 2019).…”
Section: Effect Of Manure Application On the Source Signaturesmentioning
confidence: 99%
“…Data availability. Data are available at https://doi.org/10.17605/ OSF.IO/QPRJZ (Ibraim et al, 2019).…”
Section: Effect Of Manure Application On the Source Signaturesmentioning
confidence: 99%
“…The indicated numbers were chosen for the described experiments. b) The mini QC-TILDAS spectrometer is used in combination with a preconcentration device (Ibraim et al, 2018), the indicated N2O 5 concentration range is prior to preconcentration. c) The preconcentrationmini QC-TILDAS system is used in a repetitive batch cycle without a continuous sample gas flow (Ibraim et al, 2018(Ibraim et al, , 2019.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…A compact mini QCLAS device (CW-QC-TILDAS-76-CS; ARI, USA) coupled with a preconcentration system, called trace gas extractor (TREX) was provided by Empa, Switzerland. The spectrometer comprises a continuous-wave mid-infrared quantum cascade laser source emitting at 2203 cm -1 and an 15 astigmatic multipass absorption cell with a path length of 76 m and a volume of approximately 620 cm 3 (Ibraim et al, 2018) (Table 1). The TREX unit was designed and manufactured at Empa and is used to separate the N2O from the sample gas prior to QCLAS analysis.…”
Section: Trex-qclasmentioning
confidence: 99%
See 2 more Smart Citations